Beware of glenoid dysplasia mimicking bone trauma in the injured shoulder - Seagger, Robin M. (Medknow Publications, 2009)
The term 'primary glenoid dysplasia' is used to describe a rare developmental abnormality of the shoulder. The symptomatic presentation of glenoid dysplasia has two definite age-related peaks. The first peak is in adolescents and young adults; they generally present with symptoms of instability related to high levels of activity. The second is in the fifth or sixth decade when presumed degenerative changes occur in the gleno-humeral joint. It can crop up as an incidental finding, during chest X-ray, for example, or may present as marked upper limb disability. This study reports an unusual presentation of this rare condition and describes it with clear illustrations of radiological and surgical investigations and treatment undertaken. It is presented as an 'aide-memoire' for orthopedic surgeons to consider this diagnosis when confronted with unusual X-rays or scans in their practice.